Peran Ekspor-Impor terhadap Stabilitas Pertumbuhan Ekonomi dan Neraca Berjalan - Laelaturramadani, Laelaturramadani; Rosyalita, Dita (Indonesian Journal of Research and Service Studies, 2024)
This qualitative library research investigates the role of exports and imports in maintaining the stability of economic growth and the current account balance. By synthesizing recent and reputable international literature, the study finds that exports contribute to growth through external demand and to current account stability through foreign exchange earnings. However, the stabilizing effect depends on the structure of exports; commodity dependence tends to increase volatility, while diversification and higher value-added exports improve resilience. Imports can also support growth when they consist of productive inputs—such as raw materials, capital goods, and technology—that enhance domestic productivity and export competitiveness. Conversely, import surges dominated by consumption goods may widen the trade deficit and weaken the current account, especially when external financing is unstable. Overall, external shocks, such as energy and commodity price fluctuations and supply-chain disruptions, shape the strength of these relationships. Policy implications emphasize making imports productive and strengthening sustainable, diversified exports.